Two-dimensional Janus Ti3C2FxO2-x MXene with tunable electronic and mechanical properties. (15th March 2021) - Li, Chenliang; Guo, Jing; Wang, Chaoying; Ma, Decai; Wang, Baolai
Abstract: In two-dimensional (2D) Janus materials, the asymmetric surface termination structure can significantly enhance material functionality. Here we explore the combined influence of surface termination composition and disorder on the electronic and mechanical properties of Janus T i 3 C 2 F x n O2- x ( x = 0.5, 1, or 1.5, n = 1–3). Increasing compositions of surface O atoms induce weak C- p -Ti- d coupling due to a relatively strong interaction between the surface Ti and O atoms; while the presence of F in the mixed surface termination considerably enhances the C- p -Ti- d coupling strength compared with a purely F-terminated structure. Asymmetric disordered surface functionalization influences electronic structure, creating controllable mechanical properties. Mixed surface termination leads to a significant enhancement in the elastic constant. Janus Ti3 C2 F 1 O configuration is found to possess superior flexibility, with 31% critical strain, especially useful in practical large-magnitude-strain engineering. Our results provide a strategy to tune the electronic and mechanical properties of 2D materials. Graphical abstract: Image, graphical abstract